Evaluation of the Rain Anomaly Index for the central region of the State of Espírito Santo (Research, Society and Development, 2021)
Climatic indices such as the Rain Anomaly (RAI) allow the development of monitoring systems for dry or rainy periods and facilitate the communication of information on climatic anomalies to different sectors of society. In this sense, the objective of this work was to evaluate the RAI of the central region of the State of Espírito Santo considering the methodology proposed by Rooy (1965) and adapted by Freitas (2004) and Araújo (2009). The RAI of the adopted stations was compared with the parameters of the Natural Zones of Espírito Santo (Espírito Santo, 1999). Additionally, in order to verify the impacts that the global climate causes on the regional rainfall distribution, possible influences of El Niño (EN) and La Niña (LN) on the obtained IAC values were considered. The results indicate changes in rainfall patterns in the region, apparent contradictions in relation to the natural zoning of Espírito Santo and, last but not least, remarkable rainfall variability in the evaluated stations, circumstances that reveal that it is imperative to carry out more climatological research in the region focusing on rainfall. The average IAC in the study area points to an increase in the occurrence of severe events, a particularly important finding in view of the possible negative implications in the socioeconomic chain of the region, as well as the potentially associated socio-environmental disasters.